TINGKAT PENGETAHUAN KARYAWAN KELAPA SAWIT (Elaeis guineensis Jacq.) TENTANG PEMANENAN DI PT. SAWIT SUKSES SEJAHTERA - Mohammad Yogi Hidayatullah Zain; Rossy Mirasari; Rusmini Rusmini (Politeknik Pertanian Negeri Samarinda, 2021)
This research is motivated by the importance of knowledge of an employee, especially harvest employees in order to obtain maximum FFB, it encourages researchers to determine the level of knowledge about harvesting. Therefore, the purpose of this study is to identify the characteristics of harvest employees and determine the level of knowledge of harvest employees about harvesting techniques and harvesting tools used.Collecting data in the research in the form of questionnaires and interviews, the method used is descriptive analysis to describe the level of knowledge of harvesting employees based on the frequency distribution of respondents' answers and responses to questions in the questionnaire.Characteristics of respondents at PT Sawit Sukses Sejahtera based on age at most, namely those aged over 35 years with a percentage of 68%, from education the most, namely elementary school with a percentage of 77%, based on work experience at most 1-5 years with a percentage of 41%. The respondent's level of knowledge on harvesting techniques is in the